Multivariate Statistical Analysis Based on Random Matrix to Explore the Promotion Effect of Network Resource Sharing Mode on Physical Education - Ding, Bin; Jian, Yanchun; Yuan, Xingliang (Mathematical problems in engineering, 2022)
Multivariate statistical analysis is a new statistical method emerging in recent years. Due to the continuous update and continuous development of Internet technology, statistical analysis of data from all walks of life is required. The method of multivariate statistics was soon applied to all walks of life, bringing great convenience to people’s work and industry. The method of multivariate statistics is used to process and evaluate the data, guide the school’s physical education work, and make suggestions for various functional units. This paper focuses on the multivariate statistical analysis of principal components and factors, uses factor analysis to comprehensively evaluate college students, and uses the variance method to make statistics on the four-year physical education performance of 141 undergraduates in grades 13 and four subjects. And based on this, the effect of different majors on their academic achievement is discussed. This paper believes that in college physical education, this method should be applied to daily physical education, and students should be rationally analyzed and scientifically evaluated. This model can make a comprehensive investigation of the education work so that their education work can be improved more effectively, and sports talents in colleges and universities can get better development.